Sub-Antarctic glacier extensions in the Kerguelen region (49°S, Indian Ocean) over the past 24, 000 years constrained by 36Cl moraine dating. (15th April 2017) - Jomelli, Vincent; Mokadem, Fatima; Schimmelpfennig, Irene; Chapron, Emmanuel; Rinterknecht, Vincent; Favier, Vincent; Verfaillie, Deborah; Brunstein, Daniel; Legentil, Claude; Michel, Elisabeth; Swingedouw, Didier; Jaouen, Alain; et al.
Abstract: Similar to many other regions in the world, glaciers in the southern sub-polar regions are currently retreating. In the Kerguelen Islands (49°S, 69°E), the mass balance of the Cook Ice Cap (CIC), the largest ice cap in this region, experienced dramatic shrinking between 1960 and 2013 with retreat rates among the highest in the world. This observation needs to be evaluated in a long-term context. However, data on the past glacier extents are sparse in the sub-Antarctic regions. To investigate the deglaciation pattern since the Last Glacial Maximum (LGM) period, we present the first 13 cosmogenic 36 Cl surface exposure ages from four sites in the Kerguelen Islands. The 36 Cl ages from erratic and moraine boulders span from 24.4 ± 2.7 ka to 0.3 ± 0.1 ka. We combined these ages with existing glacio-marine radiocarbon ages and bathymetric data to document the temporal and spatial changes of the island's glacial history. Ice began to retreat on the main island before 24.4 ± 2.7 ka until around the time of the Antarctic Cold Reversal (ACR) period (∼14.5–12.9 ka), during which the Bontemps moraine was formed by the advance of a CIC outlet glacier. Deglaciation continued during the Holocene probably until 3 ka with evidence of minor advances during the last millennium. This chronology is in pace with major changes in δ 18 O in a recent West Antarctica ice core record, showing that Kerguelen Islands glaciers are particularly sensitive and relevant to document climate change in the southern polar regions. Highlights: Few cosmogenic ages are available in the sub-Antarctic region. We present 13 cosmogenic 36 Cl surface exposure ages from the Kerguelen Islands. The 36 Cl ages from erratic and moraine boulders span from 24.4 ± 2.7 ka to 0.3 ± 0.1 ka. Glaciers retreated during the Late Glacial with an interruption during the ACR period. Glaciers readvanced during the last millennium.